2019
DOI: 10.1111/febs.14921
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structures of a putative periplasmic cystine‐binding protein from Candidatus Liberibacter asiaticus: insights into an adapted mechanism of ligand binding

Abstract: The amino acid‐binding receptors, a component of ABC transporters, have evolved to cater to different specificities and functions. Of particular interest are cystine‐binding receptors, which have shown broad specificity. In the present study, a putative periplasmic cystine‐binding protein from Candidatus Liberibacter asiaticus (CLasTcyA) was characterized. Analysis of the CLasTcyA sequence and crystal structures in the ligand‐bound state revealed novel features of CLasTcyA in comparison to related proteins. On… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…As yet, there are no molecular structures for Ca. L. solanacearum proteins reported and structures from Liberibacter species in general are limited (Jiang et al 2014;Saini et al 2018;Kumar, Kesari, et al 2019;Kumar, Dalal, et al 2019;Nan et al 2020), which hinders our understanding of the biology of this genus. This investigation to express, purify and characterise the 'Candidatus Liberibacter solanacearum' lysine biosynthetic enzyme dihydrodipicolinate synthase, which is well studied in other bacterial systems, provides a unique opportunity to assess how evolution shapes enzymes in context of a reduced genome and a bottlenecked lifestyle.…”
Section: Discussionmentioning
confidence: 99%
“…As yet, there are no molecular structures for Ca. L. solanacearum proteins reported and structures from Liberibacter species in general are limited (Jiang et al 2014;Saini et al 2018;Kumar, Kesari, et al 2019;Kumar, Dalal, et al 2019;Nan et al 2020), which hinders our understanding of the biology of this genus. This investigation to express, purify and characterise the 'Candidatus Liberibacter solanacearum' lysine biosynthetic enzyme dihydrodipicolinate synthase, which is well studied in other bacterial systems, provides a unique opportunity to assess how evolution shapes enzymes in context of a reduced genome and a bottlenecked lifestyle.…”
Section: Discussionmentioning
confidence: 99%
“…These facts could explain why TcyABC might be able to accommodate both CSSC and Cys in its substrate-binding site. Further studies will provide insight into the flexible substrate-binding site of TcyABC, but TcyA has been crystalized and the structure has been determined with either CSSC or Cys bound to the binding site, revealing that it has affinity for both derivatives (54).…”
Section: Discussionmentioning
confidence: 99%
“…Crystal structure and binding studies of CLasTcyA by SPR and microscale thermophoresis (MST) showed a maximum affinity with cystine ligand. Detailed crystal structure analysis of CLasTcyA showed some unique features, like a relatively larger binding pocket, presence of an extended c-terminal loop stabilized by a disulfide bond, and involvement of residue from the hinge region in the stabilization of the ligand [ 145 ]. Biophysical characterization of mutant CLasTcyA confirmed this unique feature.…”
Section: Triangular Management Strategiesmentioning
confidence: 99%
“…In C Las, only two specific periplasmic amino-acid-binding proteins are present: one is cationic amino acid, and another is CLasTcyA. Based on the unique feature of CLasTcyA and the presence of permease, it was hypothesized that CLasTcyA might be involved in the transport of cystine and other branched-chain amino acids [ 145 ]. Insilico structure-based inhibitor screening against CLasTcyA showed five compounds in the zinc database (ZINC000000211883, ZINC000004707227, ZINC000013843286, ZINC000018063863, and ZINC000100640093) that exhibit higher binding energy than the ligand molecule [ 146 ].…”
Section: Triangular Management Strategiesmentioning
confidence: 99%